2012
DOI: 10.1159/000331140
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Specific Th1 Responses and Suppression of IgE Antibody Formation by Vaccination with Plasmid DNA Encoding Cyn d 1

Abstract: Background: DNA vaccines encoding allergens have been developed to prevent or to treat specific IgE responses. Objective: To evaluate the potential preventive and therapeutic effect of DNA vaccines encoding Cyn d 1 alone or combined with different adjuvants on specific allergies. Methods: Recombinant plasmid Cyn d 1 (pCyn d 1) was constructed by insertion of Cyn d 1 cDNA into the vector pcDNA3. BALB/c mice were injected with pCyn d 1 alone or plus adjuvants such as bupivacaine, bestatin, liposome, or CpG. Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 71 publications
(97 reference statements)
1
9
0
Order By: Relevance
“…1113 We also found that the prophylactic effect of vaccination on allergic reaction in neonatal mice is similar to that in adult animal models. 12…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…1113 We also found that the prophylactic effect of vaccination on allergic reaction in neonatal mice is similar to that in adult animal models. 12…”
Section: Discussionmentioning
confidence: 61%
“…9,10 DNA vaccines have been shown to activate Th1 responses. 1115 In contrast to protein vaccines, DNA vaccines induce long-lasting intracellular expression of recombinant allergens and generate specific Th1 cells that secrete predominantly interferon (IFN) γ. 13–16 IFN-γ selectively inhibits the activation of Th2 cells and B cells, which in turn results in reduced IgE production.…”
mentioning
confidence: 99%
“…Allergens that are chemically coupled to virus-like particles [65,66] Genetic vaccines DNA vaccines -Vaccination with allergen-encoding DNA [88][89][90][91][92][93] RNA vaccines -Vaccination with allergen-encoding RNA [94] B. Alternative routes Sublingual -Sublingual administration of allergen-containing drops or tablets [17,24,[74][75][76][77][78][79] Oral -Oral administration of allergens (i.e.…”
Section: Coupled Allergensmentioning
confidence: 99%
“…Two studies performed in murine allergy models were the first to indicate that vaccination with allergen‐encoding DNA may represent a new approach for SIT [88, 89]. It has been demonstrated that genetic immunization induces allergen‐specific Th1 immune responses that may prevent allergic sensitization and eventually ongoing allergic immune responses [90, 91]. The advantage of using allergen‐encoding DNA instead of allergen for vaccination is, however, outweighed by the concern that genetic immunization may induce an uncontrolled production of allergens in treated subjects and thus may cause side effects [92].…”
Section: Genetic Immunizationmentioning
confidence: 99%
“…Vaccination with plasmid DNA encoding the major Bermuda grass pollen allergen Cyn d 1 was used in combination with different adjuvants such as bupivacaine, bestatin, liposome or CpG and induced Th1 responses associated with IgG2a responses in mice. This vaccine prevented the induction of IgE responses and also suppressed ongoing IgE production in a murine model [49].…”
Section: Other Strategiesmentioning
confidence: 99%